1999
DOI: 10.1088/0022-3727/32/12/302
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of radiofrequency magnetron sputter deposited SiO2thin films

Abstract: The SiO 2 thin-film structure deposited by radiofrequency (rf) magnetron sputtering was found to depend on whether the native oxide on the Si(111) was removed or not. X-ray reflectivity (XRR) data show that, when deposited on a clean Si(111) surface, the SiO 2 thin film consistently has a two-layer (an overlayer and an interface layer) structure. The interfacial structure depends on the deposition temperature. The film deposited at room temperature has a lower-density interface layer. With increase of the subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…But the SiO 2 layer on type 2 substrate was prepared by sputtering technique at room temperature. Brunet-Bruneau et al investigated the properties of evaporated SiO 2 films by using infrared ellipsometry and found that such a deposited SiO 2 film had a complex structure with lower density (even lower than fused silica) and possessed high pore volume fraction. , The newly deposited SiO 2 film also undergoes a loose contact at the interface and exhibits inhomogeneous structure . Therefore, we speculate that the newly deposited SiO 2 film (type 2 substrate) is in some degree similar to the porous catalyst support materials (such as porous SiO 2 , Al 2 O 3 , and MgO) commonly used for bulk growth of SWNTs. ,, Such a loose and porous SiO 2 layer can protect catalyst particles from aggregation and provide more suitable catalyst nanoparticles for SWNT growth. , This point can be confirmed by the AFM results, as shown in parts c and d of Figure .…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…But the SiO 2 layer on type 2 substrate was prepared by sputtering technique at room temperature. Brunet-Bruneau et al investigated the properties of evaporated SiO 2 films by using infrared ellipsometry and found that such a deposited SiO 2 film had a complex structure with lower density (even lower than fused silica) and possessed high pore volume fraction. , The newly deposited SiO 2 film also undergoes a loose contact at the interface and exhibits inhomogeneous structure . Therefore, we speculate that the newly deposited SiO 2 film (type 2 substrate) is in some degree similar to the porous catalyst support materials (such as porous SiO 2 , Al 2 O 3 , and MgO) commonly used for bulk growth of SWNTs. ,, Such a loose and porous SiO 2 layer can protect catalyst particles from aggregation and provide more suitable catalyst nanoparticles for SWNT growth. , This point can be confirmed by the AFM results, as shown in parts c and d of Figure .…”
Section: Resultsmentioning
confidence: 77%
“…25,26 The newly deposited SiO 2 film also undergoes a loose contact at the interface and exhibits inhomogeneous structure. 27 Therefore, we speculate that the newly deposited SiO 2 film (type 2 substrate) is in some degree similar to the porous catalyst support materials (such as porous SiO 2 , Al 2 O 3 , and MgO) commonly used for bulk growth of SWNTs. 3,5,28 Such a loose and porous SiO 2 layer can protect catalyst particles from aggregation and provide more suitable catalyst nanoparticles for SWNT growth.…”
Section: Resultsmentioning
confidence: 93%